Preventative and therapeutic potential of tocotrienols on musculoskeletal diseases in ageing - Saud Gany, Siti Liyana; Chin, Kok-Yong; Tan, Jen Kit; Aminuddin, Amilia; Makpol, Suzana (Frontiers in Pharmacology, 2023)
Musculoskeletal health is paramount in an ageing population susceptible to conditions such as osteoporosis, arthritis and fractures. Age-related changes in bone, muscle, and joint function result in declining musculoskeletal health, reduced mobility, increased risk of falls, and persistent discomfort. Preserving musculoskeletal well-being is essential for maintaining independence and enhancing the overall quality of life for the elderly. The global burden of musculoskeletal disorders is significant, impacting 1.71 billion individuals worldwide, with age-related muscle atrophy being a well-established phenomenon. Tocotrienols, a unique type of vitamin E found in various sources, demonstrate exceptional antioxidant capabilities compared to tocopherols. This characteristic positions them as promising candidates for addressing musculoskeletal challenges, particularly in mitigating inflammation and oxidative stress underlying musculoskeletal disorders. This review paper comprehensively examines existing research into the preventive and therapeutic potential of tocotrienols in addressing age-related musculoskeletal issues. It sheds light on the promising role of tocotrienols in enhancing musculoskeletal health and overall well-being, emphasizing their significance within the broader context of age-related health concerns.